Netwerk Center for Contemporary Art : Annual 2007. - Lambion, Emmanuel; Roelstraete, Dieter; Truong, Hong-An; Van Damme, Bram (Aalst : Netwerk / centrum voor hedendaagse kunst Aalst, 2008)
de Vries, Jan ; 51N4E ; De Bruyn, Goele ; De Clercq, Anouk ; Dedobbeleer, Koenraad ; Dheedene, Stefaan ; D'Hondt, Lieve ; Denicolai, Simona ; Provoost, Ivo ; Fink, Christoph ; Geurts, Frederic ; Goiris, Geert ; Jacobs, Aernoudt ; Koeman, Jean Bernard ; van Nes, Boris ; Verhaegen, Hans ; Voet, Leen ; Guiot, Nicolas ; Bailly, Virginie ; Hayeur, Isabelle ; Raymond, Eric ; Posehn, Kristin ; Brellochs, Mari ; Chong, Heman ; Chodzinski, Armin ; Friess, Barbara ; Hoesle, Adi ; Feigl, Florian ; Galeazzi, Nicolas ; Reinigungsgesellschaft ; Van Lierde, Jan ; Zwierzynska, Agata ; Evrard, David ; Heiremans, Ronny ; Vermeir, Katleen ; Huyghebaert, Pierre ; Leech, Adam ; Meessen, Vincent ; de Boeck, Lieven ; Liefooghe, Laurent ; Langsdorf, Heike ; Sickle, Ula ; Abdul, Lida ; Albers, Beatrijs ; Timmermans, Reggy ; Anesiadou, Danai ; Bryssinck, Hans ; Peeters, Diederik
CD in speciale kast
Engels
Nederlands
boek